Determination OF DIFFERENT STORAGE TECHNIQUES and shelf life on ONION (Allium sepa L.) bulbs - Lanzai H. A.; Abubakar A.; Mohammed U. A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Onion (Allium cepa L.) is the most economically important Allium crop. Estimates of post-harvest loss in onions exceeds 30 percent, significantly reducing farmer's income. This research evaluates the effectiveness of some low-cost farm storage technologies. Doum Palm Fruit Storage Techniques (DPFST), Neem leave and riverbed sand were evaluated for loss in weight (LW %), rotting %, sprouting %, damage of black moulds and healthy onios. These parameters were taken at intervals of 15, 30, 45, 60, 75 and 90 days after storage (DAS). The mean LW% of the bulbs irrespective of storage condition increased from 3.00 percent at 15 DAS to 13.60 percent at 90 DAS. The mean percentage rotting of bulbs irrespective of storage methods increased from 0.6 at 30 DAS to 8.25 at 90 DAS. Minimum per cent black mould was noticed in bulbs stored in riverbed sand. No sprouting was recorded in all treatments until 30 days after storage. Maximum percent of healthy bulbs were recorded in bulbs stored in DPFST. The results obtained revealed that both DPFST and riverbed sand storage structure are highly effective and significantly prolong the shelf-life of onions, hence recommended for use to farmers.